Leadership quality and transformational plan are an important predictors for the integrity level among employees of Malaysian anti corruption Agency (MACC) - Darus, Amer; Ahmed, Faiz; Alhaderi, Sami; Azimi, Afeefa (2017)
The main purpose of this study is to identify the staffs’ integrity level of Human Resource and Administrative Department (BPSMPA), Malaysian Anti-Corruption Commission (MACC), and the factor(s) that influencing their integrity level the most. Other objectives include to examine the relationships between the factors and their integrity level; and to examine the underlying demography factors that could predict their integrity level.Data were collected through a survey of 104 respondents.Analysis of the quantitative data suggests that the integrity level of BPSMPA, MACC staffs is at ordinary level which proposes factors that influenced their integrity level the most are religiosity, job performance, and leadership quality.The presences of leadership quality, religiosity, job performance, along with the transformational plan are significantly associated with their integrity level.The results also suggest that the relative importance of respondents’ year of employment in predicting integrity level differed according to the integrity domains.This research does generalized BPSMPA staffs’ integrity level and its relationship with leadership quality, religiosity, job performance, and transformational plan.Therefore, this study could be replicated in other enforcement agencies in order to find the non enforcement staffs’ integrity level.